The clause in English : in honour of Rodney Huddleston - Huddleston, Rodney D.; Collins, Peter, 1950-; Lee, David (David A.) (Studies in language companion series, 1999)
The focus in this volume is on grammatical aspects of the clause in English, presenting a fine balance between theoretically- and descriptively-oriented approaches. Some authors investigate the status and properties of 'minor' or 'fringe' constructions, including 'deictic-presentationals'; non-restrictive relative clauses with that; 'isolated if-clauses', and 'exceptional clauses'. In some articles the validity of conventional accounts and approaches is questioned: such as traditional constituency trees and labelled bracketings as a means of representing relationships between parenthetical ele.